2022
DOI: 10.1039/d1an02147h
|View full text |Cite
|
Sign up to set email alerts
|

Lighting up of carbon dots for copper(ii) detection using an aggregation-induced enhanced strategy

Abstract: Carbon dots have promising prospects for analytical and monitoring purposes but are greatly hindered by the aggregation-induced luminescence quenching owing to the π-π interaction or the non-radiation-excited radical complex formation....

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Through the comparison of the differences between DN-CDs, N-CDs-1 and N-CDs-2, the ratio of N and O atoms were found to be a potential reason for the ability to detecting Cu 2+ and Fe 3+ ions. Table S1 summarized the detection parameters for the selective detection of metal ions (Cu 2+ and Fe 3+ ) with the different N-doped carbon dots [66][67][68][69][70][71][72][73][74][75][76][77][78][79]. It could be found that although N-doped carbon dots contained different electron-rich functional groups, we suggest that the proportion of the N, O atoms might affect the selectivity towards Cu 2+ and Fe 3+ ions.…”
Section: Discussion On the Selectivity Of Cu 2+ And Fe 3+ Ionsmentioning
confidence: 97%
“…Through the comparison of the differences between DN-CDs, N-CDs-1 and N-CDs-2, the ratio of N and O atoms were found to be a potential reason for the ability to detecting Cu 2+ and Fe 3+ ions. Table S1 summarized the detection parameters for the selective detection of metal ions (Cu 2+ and Fe 3+ ) with the different N-doped carbon dots [66][67][68][69][70][71][72][73][74][75][76][77][78][79]. It could be found that although N-doped carbon dots contained different electron-rich functional groups, we suggest that the proportion of the N, O atoms might affect the selectivity towards Cu 2+ and Fe 3+ ions.…”
Section: Discussion On the Selectivity Of Cu 2+ And Fe 3+ Ionsmentioning
confidence: 97%
“…7c and d. Zhang et al 112 prepared orange-yellow quantum dots through a solvothermal method, which can be used to detect Cu 2+ . The fluorescence intensity increased with increasing concentration of Cu 2+ , as displayed in Fig.…”
Section: Biosensingmentioning
confidence: 99%
“…As an emerging class of photoluminescent quantum dots, QDs have become the focus of nanomaterials because of their special photoelectric properties, excellent biocompatibility and stability. [9][10][11][12] Compared with traditional III-V (InAs, GaSb, and GaN) 13 , II-VI QDs (CdSe, ZnSe, and CdTe) 14 and other nanoparticles, [15][16][17] silicon quantum dots (SiQDs) have unique properties 18,19 including innocuousness, greenness, low cost, and high sensitivity and selectivity. Importantly, SiQDs also have the benets of good biocompatibility because they can be converted by the kidneys into silicates and excreted in the urine.…”
Section: Introductionmentioning
confidence: 99%